2016
DOI: 10.1590/s0100-736x2016001000011
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose and bacterial cellulose/polycaprolactone composite as tissue substitutes in rabbits' cornea

Abstract: In order to test the performance of bacterial cellulose/polycaprolactone composite (BC/PCL) and pure bacterial cellulose (BC) as tissue substitutes in rabbits' cornea, a superficial ulcer containing 5mm in diameter and 0.2mm deep was made in the right cornea of 36 rabbits, then a interlayer pocket was created from the basis of this ulcer. Twelve rabbits received BC/PCL membrane and 12 were treated with BC membranes, both membranes with 8mm in diameter. The remaining rabbits received no membrane constituting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
(32 reference statements)
0
18
1
Order By: Relevance
“…As BC has a porous structure and fibre arrangement, it acts as a support for a variety of reinforcements. The attached particles provide additional properties (antibacterial, transparency, resistance) to BC that enhance its natural biological and physiochemical properties (Yang et al 2012;Sepúlveda et al 2016).…”
Section: Soft Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…As BC has a porous structure and fibre arrangement, it acts as a support for a variety of reinforcements. The attached particles provide additional properties (antibacterial, transparency, resistance) to BC that enhance its natural biological and physiochemical properties (Yang et al 2012;Sepúlveda et al 2016).…”
Section: Soft Tissue Engineeringmentioning
confidence: 99%
“…Corneal injuries and ulcers require emergency keratoplasty to restore eye integrity and prevent complications (Sepúlveda et al 2016). Ocular destructive processes (lacrimal abnormalities and traumas) determine ulcerative keratitis, which gives high morbidity (Macedo et al 2010).…”
Section: Soft Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no study so far has dealt with the behavior of epithelial cells on BC. Moreover, the sole in vivo study on the use of BC for cornea replacement, performed by Sepúlveda, demonstrated moderate inflammatory response (Sepúlveda et al 2016), which contradicted with the in vitro studies. Therefore, there is an urgent need to verify the feasibility of BC as the cornea scaffold material.…”
Section: Introductionmentioning
confidence: 85%
“…Unlike many previous works that conducted in vitro experiments, we conducted in vivo studies by adopting a protocol to further confirm the feasibility of BC as cornea scaffold material, which was different from that employed by Sepúlveda et al who demonstrated moderate inflammatory process during the clinical observation after BC implantation (Sepúlveda et al 2016). In Sepúlveda's work, a corneal ulcer was inflicted firstly, and an interlayer pocket from the base of the ulcer was made afterwards, for insertion and positioning of the membranes in the animals that received the membranes.…”
Section: Discussionmentioning
confidence: 99%